1998
DOI: 10.1007/bf02466220
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of temporary use of pipe bends of steam power plants damaged by creep pores

Abstract: In the operation of the power equipment of steam power plants the steam pipe bends can be damaged at a temperature exceeding 500~ The presence of creep pores (especially pore chains) in the metal of a bend operating for a long time indicates that the service life of the bend has been exhausted. However, it remains unclear whether it is possible to use it again and when it should be replaced. The present analysis of the results of a study of the metal of damaged bends makes it possible to determine the possibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In [9], data of studies are presented in which the period of time was observed (for seven cases) for which single pores developed to chains of pores in the tensile zone of bends that are in operation. It was found in the course of long term observations that under the oper ating conditions of metal (at a temperature of 540-555°С, stresses ranging from 60 to 80 MPa, and oper ating time equal to 80000-140000 h), this period of time makes from 2500 to 30000 h. In this connection, the period of time from the incipience of individual pores to the occurrence of pore chains was selected as a check one for making a comparison between the results of field observations and results of calculations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In [9], data of studies are presented in which the period of time was observed (for seven cases) for which single pores developed to chains of pores in the tensile zone of bends that are in operation. It was found in the course of long term observations that under the oper ating conditions of metal (at a temperature of 540-555°С, stresses ranging from 60 to 80 MPa, and oper ating time equal to 80000-140000 h), this period of time makes from 2500 to 30000 h. In this connection, the period of time from the incipience of individual pores to the occurrence of pore chains was selected as a check one for making a comparison between the results of field observations and results of calculations.…”
mentioning
confidence: 99%
“…Notched samples with ω 0 = 0.65 were selected as the basic ones proceeding from the data of [9], in which it was revealed that in the bends on which cracks were found pore chains propagated to exactly this rel ative depth. The smooth part of the samples had a diameter of 16 mm, and their annularly notched part had a diameter of 9.4 mm.…”
mentioning
confidence: 99%